Magnetic Carbon Nanotubes/Graphene Oxide Nanocomposites: One-Step Controllable Production, and Their Excellent Microwave Absorption Capabilities - Wu, Mei; Qi, Xiaosi; Xie, Ren; Qin, Shuijie; Deng, Chaoyong; Zhong, Wei (Frontiers in Materials, 2020)
In this research, three-dimensional (3D) hierarchical networks of magnetic carbon nanotubes/graphene oxide (CNTs/GO) nanocomposites (NCs) were synthesized by a one-step hydrothermal method with the idea of constructing more interface contacts, a double loss mechanism and synergy effect. The obtained results showed that the content of NCs gradually transitioned from CoCO3 to CoxFe3–xO4. Further, CoCO3-CoxFe3–xO4/CNTs/GO quaternary NCs and CoxFe3–xO4/CNTs/GO ternary NCs could be selectively synthesized when the Co:Fe molar ratio decreased from 1:1 to 1:3. The as-prepared samples displayed excellent microwave absorption properties (MAPs) in terms of the minimum reflection loss (RLmin) and the corresponding absorption bandwidth (FBcor) with reflection loss values lower than −10 dB. The RLmin and large FBcor values for the as-prepared samples were −54.69 dB and 2.36 GHz, −63.99 dB and 2.48 GHz, −63.36 dB and 2.68 GHz, respectively. The designed 3D hierarchical networked structure of magnetic GO/CNTs NCs displayed outstanding comprehensive MAPs, which could deliver a practical and effective strategy to develop high-performance microwave absorbers (MAs), considering their low cost, lightweight, and high stability.